Celiacomesenteric trunk: a rare case - Tek, Cihat; Aydın, Sonay; Ergün, Elif; Koşar, Pınar Nercis (The European Research Journal, 2018)
We present a case of celiacomesenteric trunk that was incidentally detected on routine multi-detector row computed tomography angiography of lower extremities. A 59-year-old patient had intermittent claudication. The celiacomesenteric trunk is a rare vascular variation that is important to be detected before surgical and interventional procedures. Multi-detector row computed tomography angiography is excellent on showing vascular anatomy, pathology and variations.